Mechanisms of Vertical Mixing Over the Shelf Region in the Southwestern Arafura Sea - Muhammad Raafi; Yuli Naulita; I Wayan Nurjaya; Rastina (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2026)
Vertical mixing regulates nutrient supply and productivity in surface layer, yet the controlling mechanisms remain unclear. Over shelf regions such as the southwestern Arafura Sea, steep topography and strong semidiurnal tides suggest that internal tide topography interactions may enhance turbulence. Unfortunately, observational links among stratification, topographically driven mixing processes, and internal tides remain limited in this region. This study investigates the dominant mechanisms controlling vertical mixing over the shelf region using hydrographic profiles, indirect turbulent measurements, and internal-tide diagnostics. We examined the stability, water masses, and turbulent kinetic energy dissipation rate (ε) and vertical eddy diffusivity (Kρ) from Thorpe-scale overturns. Internal-tide influence was assessed through M2 ray path modeling and by sampling the M2 tidal envelope at CTD cast times. Results show that the 50-200 m thermocline forms a barrier that suppresses mixing offshore and on the shelf, where Kρ generally remains below 10⁻⁴ m² s⁻¹. Along the slope, weaker stratification at 600-1,000 m supports large overturns and elevated ε (10⁻⁷-10⁻⁸ W kg⁻¹). Ri# indicates weak background shear, while Tu identifies salt-finger–favorable conditions contributing to mid-depth mixing. The spatial alignment between elevated ε and the shifted M2 envelope, consistent with M2 ray path geometry, suggests that internal tides reflected from locally supercritical topography enhance turbulence at the slope. These findings highlight the slope as a focused mixing hotspot. Future work should use moored velocity and high-resolution models to better resolve internal-tide energy pathways and their biogeochemical impacts.